The Use Of Finstagram As A Platform For Self-Disclosure - Fikry Zahria Emeraldien; Amanda Diva Aulia; Yustika Okta Khelsea (Jurnal Ilmu Komunikasi, 2019)
In this era, self-disclosure is not only done in face-to-facecommunication, but can also be done through social media platforms, one of whichis Instagram. By utilizing the Johari Window concept, this study aims to find outhow the use of the second Instagram account or commonly called Finstagram (fakeInstagram) as a form of self-disclosure by UPN "Veteran" Jawa Timur students.This is a qualitative research with interview as data collection technique. In additionto interview, observation or analyzing posts on the student’s Finstagram account isalso done by researchers. The results showed that UPN "Veteran" Jawa Timurstudents used Finstagram account to express their self-disclosure. They are moreopen when uploading various photos, videos, and telling information on theirFinstagram account. The Finstagram accounts they make are only followed byfriends who they know or they are close to, thus they can upload everything.Finstagram becomes a place to pour out the feelings that are being experienced.They assume that their followers in the Finstagram account can accept their trueself.Finstagram is a stage or platform for students to express honesty and selfdisclosure.The self-disclosure occurs in four areas stated in the Johari Windowconcept, namely open area, blind area, hidden area, and unknown area.